Meningkatkan Hasil Belajar Peserta Didik Melalui Model Problem Based Learning pada Mata Pelajaran PPKn Kelas XII IPS 1 di SMA Negeri 2 Rantau Utara - Bella Indriana (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine the improvement of learning outcomes of class 12 IPS 1 students in PPKN subjects at SMA Negeri 2 Rantau Utara through the problem based learning model. The method used in this study is classroom action research (CAR), the subjects of the study were 35 class 12 IPS 1 students. The focus of this study is the learning outcomes of class 12 IPS 1 students in PPKn subjects with indicators of student learning success that reach KKM (minimum completion criteria) with a value of 82. The results of the study indicate that the application of the problem based learning model is effective in improving student learning outcomes in PPKn subjects. This increase can be seen from the pre-action stage, only 10 people with a percentage of 28.6% have met the minimum completion criteria (KKM), then in cycle I there were 18 people with a percentage of 51.4%, while in cycle II there were 29 people with a percentage of 82.82% of students have reached KKM. From these results, it can be concluded that the problem-based learning model is able to improve student learning outcomes, not only cognitively but also improve critical thinking skills, cooperation, and increase student self-confidence.